A matter of commitments - New Sunday Times, Intan Maizura Ahmad Kamal (2009)
Without warning, the dark clouds roll in. From posing prettilt for the camera, three-year-old Lily Maryam's face suddenly contorts with unbridled rage as she lunges at her mother, who had been getting herself into position with her husband for a special pose for photographer Rohanis Shukri.